A Simple Sequence Repeat (SSR) marker comparison of a large in- and ex-situ potato landrace cultivar collection from Peru reaffirms the complementary nature of both conservation strategies - Haan, Stef de; Nunez, J.; Bonierbale, Merideth W.; Ghislain, M.; Maesen, J. van der (MDPI, 2013)
An enhanced understanding of the temporal dynamics of intraspecific diversity is anticipated to improve the adequacy of conservation priorities, methods and metrics. We report on the comparative genetic composition of ex- and in-situ landrace cultivar populations from a potato diversity hotspot in the Andes. A total of 989 landrace cultivars belonging to contemporary custodian-farmer in situ collections from central Peru were compared with 173 accessions from a spatially analogous, but temporally differential ex situ composite genotype reference (CGR) set using 15 nuclear microsatellite markers. A total of 173 alleles were detected, with 129 alleles (74.6%) being shared between both populations. Both populations contain exclusive allelic diversity with 32 and 12 unique alleles belonging to the ex- and in-situ population, respectively. The mean unbiased expected heterozygosity values of the ex- and in-situ population are very similar, 0.749 versus 0.727, with a slightly wider range and standard deviation encountered for the in situ population. Analysis of Molecular Variance shows that 98.8% of the total variation is found within both populations, while the fixation index (Fst = 0.01236) corroborates that the populations are not well differentiated. Surprisingly, only 41.0% of the ex situ population encounters a similar landrace cultivar in 23.4% of the in situ population at a non-stringent threshold similarity coefficient of 0.80. While the ex- and in-situ population under comparison show similarities and unique features at the allelic level, their landrace cultivar composition is surprisingly distinct. Results affirm that crop evolution is an ongoing phenomenon and that change in fixed geographies is occurring.